An application of lean management on capacity and operational processes in a comprehensive epilepsy program. (2016) - Madhavan, Deepak; Schniederjans, Marc J.; Schniederjans, Dara G.
The University of Nebraska Medical Center (UNMC) comprehensive epilepsy program has faced challenges accompanying the growth of the centre focused on optimising patient throughput and minimising wait times. Wait times in particular have been a problem due to deficiencies in infrastructural organisation and capacity for diagnostic testing. This paper focuses on the outcomes of the implementation of lean management in the UNMC comprehensive epilepsy program. Performance comparisons on wait times from the initial patient visit to VEEG monitoring (the first critical diagnostic step in determining the proper intervention for patients) are made to a post state where specific strategies drawn from lean management are utilised to construct patient flow maps that maximise value-added activities. The results show the lean management approach during the period of this study was ideal for uncovering methods to maintain clinical services while decreasing wait times as a complementary strategy for increasing diagnostic testing capacity.